2020
DOI: 10.1175/jamc-d-19-0125.1
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Case Study of Synergies between an Intense Heat Wave and the Urban Heat Island in Beijing

Abstract: The focus of this study is an intense heat episode that occurred on 9–13 July 2017 in Beijing, China, that resulted in severe impacts on natural and human variables, including record-setting daily electricity consumption levels. This event was observed and analyzed with a suite of local and mesoscale instruments, including a high-density automated weather station network, soil moisture sensors, and ground-based vertical instruments (e.g., a wind profiler, a ceilometer, and three radiometers) situated in and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 59 publications
1
49
0
Order By: Relevance
“…In contrast to the in situ measurement, thermal infrared remote sensing from satellites allows global monitoring of geophysical parameters such as land surface temperature, and thus is widely used for studying surface urban heat island [51,52]. A few studies [29,53] also used ground-based or aircraft-based remote sensors to observe the urban boundary layer (UBL). Among the various satellite images, Moderate Resolution Imaging Spectroradiometer (MODIS) (https://modis.gsfc.nasa.gov, accessed on 6 June 2021) and Landsat (https://landsat.gsfc.nasa.gov, accessed on 6 June 2021) images are commonly used [54][55][56][57][58][59].…”
Section: Remote Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the in situ measurement, thermal infrared remote sensing from satellites allows global monitoring of geophysical parameters such as land surface temperature, and thus is widely used for studying surface urban heat island [51,52]. A few studies [29,53] also used ground-based or aircraft-based remote sensors to observe the urban boundary layer (UBL). Among the various satellite images, Moderate Resolution Imaging Spectroradiometer (MODIS) (https://modis.gsfc.nasa.gov, accessed on 6 June 2021) and Landsat (https://landsat.gsfc.nasa.gov, accessed on 6 June 2021) images are commonly used [54][55][56][57][58][59].…”
Section: Remote Sensingmentioning
confidence: 99%
“…On the other hand, HWs may strongly affect the spatial and temporal variability of UHI by altering sensible and latent heat transfer and changing wind conditions [4,27,28]. While many researchers [27][28][29] have reported synergistic interactions between UHI and HW, other researchers [25,30] found no synergistic effect. Nevertheless, the interaction between UHI and HW is complex and remains a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud cover and surface humidity generally increased through the entire heatwave periods, resulting in hot days occurring ahead of hot nights. A case study suggested that the sources of the increased moisture included both local evaporation and moisture advection (An et al, 2020). Future studies will investigate the relevant mechan-isms involving the roles of land-atmosphere processes and atmospheric circulations.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can be attributed to differences in urbanization ratios. A high urbanization ratio leads to a stronger nighttime UHI during hot nights, which is related to the synergistic interaction between UHI and heat waves (An et al., 2020; Ao et al., 2019; Jiang et al., 2019; D. Li & Bou‐Zeid, 2013). This study proved that this synergy also exists at stations far away from the main urban area but have high urbanization ratios.…”
Section: Discussionmentioning
confidence: 99%